Multiple osteofibrous dysplasia combined with femoral fracture with proximal femur shepherd's crook and femoral pseudojoint formation: case report and literature review - Wang, Zongpu; Qin, Song; Wang, Tienan; Wang, Jianchuan (Frontiers in Surgery, 2025)
BackgroundOsteofibrous dysplasia is a congenital, non-hereditary benign bone disease characterized by localized bone protrusion and replacement of normal bone cancellous by proliferating abnormal bone fibers. For this case, there is no unified treatment standard for internal fixation reconstruction or replacement, which is mainly based on comprehensive evaluation of each patient's clinical history and imaging findings.Case presentationWe report a case of systemic multiple osteofibrous dysplasia complicated by left femoral bone fracture, left proximal-femur shepherd's crook deformity, and femoral pseudojoint formation. According to the patient's previous medical history and admission imaging examination, large segments of the ipsilateral fibula were removed, the bone marrow cavity was implanted, locking plate screws were inserted through the fibula in the pulp cavity, and steel cables were added to enhance stability. After 1 year of follow-up, the fracture had healed, and the patient returned to the prefracture walking state with satisfactory clinical results.ConclusionsFor rare cases of systemic multiple fibrous dysplasia combined with femoral fracture with proximal-femur shepherd's crook deformity and femoral pseudojoint formation, either internal fixation reconstruction or hip replacement, specific analysis should be performed to provide a reference for future clinical diagnosis and treatment of this disease.